FLEKSITARER OG PURISTER: Eksistensæstetiske spisepraksisser i Cambridge, Massachusetts - Bach, Dil (Tidsskriftet Antropologi, 1998)
Dil Bach: Flexitarians and Purists: Aesthetic Existential Practices of the Self in Cambridge, Massachusetts This article suggests that some of the insights developed by Foucault in his analysis of antiquity can provide an alternative perspective on modem health-oriented eating practices. The author demonstrates this through field material from Cambridge, MA, USA. In her analysis of two local natural food stores, the author shows that the stores do not impose ultimate prescriptions, but rather encourage an “aesthetics of existence”. The shoppers thus engage in voluntary “practices of the self’ in which expert advice participates in a reflexive interplay between the shoppers and their bodies. In conclusion the author notes that the aesthetics of existence should not be seen as a “pure” expression of autonomy and freedom. Not only are the expert discourses deeply embedded in commercial relations, they also forcefully place people in the role of reflexive subjects.